Thinking about Good and Evil : Jewish Views from Antiquity to Modernity - Allen, Wayne R. (Book collections on Project MUSE., 2021)
The most comprehensive book on the topic, Thinking about Good and Evil traces salient Jewish ideas about why innocent people seem to suffer, why evil individuals seem to prosper, and God's role in matters of (in)justice, from antiquity to modernity.